Cost Estimation of Structural Work for Residential Building with Seismic Design Consideration - Roslan, H. A.; Zulkhibri, N. S.; Faisal, Ade; Adiyanto, M. I. (International Journal of Integrated Engineering, 2023)
The Sumatra-Andaman earthquakes had triggered local earthquakes in Malaysia by reactivation of ancient inactive faults. Previously on 5th June 2015, Ranau, a region located in Sabah, Malaysia, had experienced a moderate earthquake of Mw6.1. The structural failures occurred because all existing buildings only designed for gravity load without any seismic provision. Recent research work exhibits the seismic designs’ impact on the cost of material and its parameters that impact the cost. There are two types reinforced concrete residential buildings called Type 1 and Type 2 for two storey and four storey which had been used as models. This research applied four seismicity levels to the reference peak ground acceleration value, ?gR = 0.07g, 0.10g, 0.13g & 0.16g, and two soil types: Soil Types B and D. The result shows that for two storey reinforced concrete residential buildings on soil types B and D, seismic design increases structural work costs, which is around 0.62% to 1.31% and 0.61% to 2.16%, respectively, for Type 1 model compared to non-seismic design. Besides, model Type 2, the increment is around 0.24% to 1.22% and 0.20% to 1.71%, respectively. Otherwise, for reinforced concrete residential building with four storey on soil types B and D, the result shows that seismic design tends to have a higher structural work’s cost around 0.41% to 2.48% and 0.98% to 11.23%, respectively, for Type 1 model. Besides, for model Type 2 the increment is around 1.80% to 2.05% and 2.34% to 8.53%, respectively, compared to nonseismic design.